Long-Run Effects of Temporary Incentives on Medical Care Productivity - Celhay, Pablo; Gertler, Paul; Giovagnoli, Paula; Vermeersch, Christel (World Bank, Washington, DC, 2015)
The adoption of new clinical practice patterns by medical care providers is often challenging, even when the patterns are believed to be efficacious and profitable. This paper uses a randomized field experiment to examine the effects of temporary financial incentives paid to medical care clinics for the initiation of prenatal care in the first trimester of pregnancy. The rate of early initiation of prenatal care was 34 percent higher in the treatment group than in the control group while the incentives were being paid, and this effect persisted at least 15 months and likely 24 months or more after the incentives ended. These results are consistent with a model where the incentives enable providers to address the fixed costs of overcoming organizational inertia in innovation, and suggest that temporary incentives may be effective at motivating improvements in long-run provider performance at a substantially lower cost than permanent incentives.